Central and Peripheral Corneal Endothelial Cell Analysis With Slit-Scanning Wide-Field Contact Specular Microscopy: Agreement With Noncontact Specular Microscopy. Issue 9 (September 2019) - Lee, Jinhee; Mori, Yosai; Ogata, Miyuki; Minami, Keiichiro; Miyata, Kazunori
Abstract : Purpose: The prospective case series aimed to examine the agreement between the use of a slit-scanning contact specular microscope and a noncontact specular microscope in corneal endothelial cell (CEC) analysis and to evaluate the differences between the central and peripheral regions in normal corneas. Methods: After confirming normal corneal endothelium with slit-lamp microscopy, CEC images of 56 eyes of 56 cataractous patients were analyzed in the central and 4 peripheral regions using a slit-scanning contact specular microscope. A noncontact specular microscope was used for the analysis in the central region. The endothelial cell density (ECD), the percentage of hexagonal shape cells (HEX), and the coefficient of variation (CV) in the central region were compared. Differences between central and peripheral CECs were also evaluated. Results: The mean ECD was 2778 cell/mm 2 and was not different from the results using the noncontact specular microscope (2736 cell/mm 2, P = 0.051). There was a significant correlation ( P < 0.001, R 2 = 0.72). The analysis of HEX resulted in larger values with the slit-scanning contact microscope (53.13% vs. 48.89%, P < 0.001), whereas there was no difference in the CV (38.48 vs. 38.04, P = 0.56). On comparing the central and peripheral regions, there was no significant difference in the ECD, whereas significant differences were found in the superior region in the HEX and CV ( P < 0.001) and in the nasal region in CV ( P = 0.023). Conclusions: The analysis of ECD with the use of the slit-scanning contact specular microscope did not differ from the noncontact specular microscope, and the results demonstrated no difference between the central and peripheral ECD.